Improving co-existence in a secondary school in the community of Madrid - Torrego Seijo, Juan Carlos (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
This article refers to the main conclusions from a secondary school research case in the Community of Madrid (Spain). The school has had an outstanding development in the improvement of school well being or “convivencia” .This initiative took place within a broader research on school innovation sponsored by the Ministry of Education of Spain through de CIDE. One of the main results is the crossing of aspects related to school innovation both as promoters and inhibitors and well being at school. The study of a case study has been the main methodology of the research project as it maintains the main aim of the research and allows us a closer contact with the reality of the school. There are different results regarding to the institutionalized processes in the implementation of a better life at school, having as a central issue the close link between improvement of school well being at school and of social relations within the students.